IMPACT OF MATERNAL NUTRITION ON CHILD HEALTH - Akhtar, Naushaba; Satapathy, Subhadarshini (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: The state of under nutrition among women in India has remained a prevalent cause for affecting maternal and child health and increasing neonatal deaths. Objective: In this paper, the authors have reviewed and summarized the complete knowledge of maternal nutrition requirements, how maternal nutrition impacts child health and public health considerations. Method: Review of existing scientific literature and records from the past. Conclusion: In this article, the author concludes that nutrition is one of those factors which can be easily modified and it is of great public health importance, giving importance to nutrition can be of great health to mother and child and reduce birth complications and adverse birth outcomes. Keywords: Nutrition, Maternal health, Maternal nutrition, Child Health, Birth outcomes.